Crescimento e marcadores bioquímicos de recém-nascido prematuro - Barreto, Grasiely Masotti Scalabrin (2017)
Prematurity is an emerging problem in global health, contributing to the infant mortality, specifically the neonatal mortality due to prenatal, maternal, fetal, and birth factors. From the advances occurred in recent decades in the maternal-fetal medicine and neonatal care have raised the survival of premature infants, increasingly with birth weight and gestational age (GA) progressively lower, this situation rise the risks of morbidity in the future. Thus, prematurity and low birth weight has been associated with changes in growth and in the metabolism of these children. In the literature, there is a gap on studies that address this issue in the population of premature infants (PT) related to the birth weight classification and it influences in their metabolic profile throughout the follow-up. It is important to investigate over the first few months of the child`s life that was born prematurely, its measures of body composition, as well as, detect the pattern of lipid, glucose and insulin metabolism of these preterm infants. In this sense, it seeks the relationship between the evolution of growth since birth and the metabolic conditions of preterm infants during their follow-up. In this context, it has as objective of the research, evaluating the growth of preterm infants from birth to six months corrected age and their lipid profile, blood glucose levels and insulin as the adequacy of birth weight. A quantitative study, observational, longitudinal, prospective study conducted in a Neonatal Intensive Care Unit and an outpatient follow-up of high risk of a University Hospital. In study 107 mothers and 115 PT was enrolled from 2015 May 1st to 2016 August 15th. 72 preterm infants have completed the follow-up at the six months of corrected age. Preterm infants were divided in two groups - Appropriate weight for gestational age (AGA) and Small for Gestational Age (SGA) and to correlate them with the results of blood glucose, triglyceride, cholesterol and insulin. Statistical analyzes were performed with the Statistica 7.0. Of the total number of preterm infants who completed the follow-up, the majority of mothers was Caucasian, with 10 to 12 years of study, annual income between 3300 to 6300 dollars, not alcoholics or smokers, the infection of urinary tract was the main morbidity during pregnancy, followed by hypertensive disease specifies of pregnancy. 88% of the PT were classified as AGA, 40% weighing between 1000 to 1499g and 45% with gestational age between 28 to 31 week. The growth of preterm newborns was linear over the follow-up, but the Z scores for weight, height and head circumference remained lower than expected for their GA. In the correlation between AGA and SGA infants and their metabolic profiles, no statistical difference between the groups were observed for cholesterol, blood glucose, and insulin, throughout the follow-up. However, the triglycerides showed ascending curve from birth, predominantly between SGA. Therefore, this group of premature constitute a population at high risk for potential cardiovascular changes in the future, as well as, delays in its growth from birth throughout the follow-up. The appropriate follow-up of these newborn babies is fundamental in order to retard, mitigate or avoid morbidities throughout their lives.